2020
DOI: 10.1371/journal.pone.0228083
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in kinematic generalization between visual and passive lead-in movements are consistent with a forward model in the sensorimotor system

Abstract: In our daily life we often make complex actions comprised of linked movements, such as reaching for a cup of coffee and bringing it to our mouth to drink. Recent work has highlighted the role of such linked movements in the formation of independent motor memories, affecting the learning rate and ability to learn opposing force fields. In these studies, distinct prior movements (lead-in movements) allow adaptation of opposing dynamics on the following movement. Purely visual or purely passive lead-in movements … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Importantly, for familiar tasks this switching is evoked immediately, without the need to re-learn the dynamics again on re-exposure. This is clearly seen on the second or later days after adapting to dual force fields [ 35 , 79 ]. In this study, our main goal was to demonstrate that such contextual switching is also possible for feedback controllers, rather than to demonstrate gradual adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, for familiar tasks this switching is evoked immediately, without the need to re-learn the dynamics again on re-exposure. This is clearly seen on the second or later days after adapting to dual force fields [ 35 , 79 ]. In this study, our main goal was to demonstrate that such contextual switching is also possible for feedback controllers, rather than to demonstrate gradual adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that our planned trajectory is based on the visual geometric information of the entire system, not just the endpoint, by using a novel mapping between finger movements and the object movement (Danziger and Mussa-Ivaldi 2012). In terms of adapting simultaneously to two opposing force fields, certain types of visual feedback can be used as a contextual cue to separate the learning of these dynamics (Forano et al 2021; Howard et al 2020; Howard et al 2012; Howard et al 2013; Howard et al 2015). The fact that only specific types of contextual information allows the learning of two opposing force fields, suggests that only specific signals trigger a switch between or access specific motor memories in a given task.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies would be needed to confirm whether these visual cues are used within state estimation as we suggest with our model. One possible test of this would be to investigate the role of these online visual cues in dual adaptation paradigms (Howard et al 2013) as we have suggested that strength of contextual cues depends on their use within state estimation (Forano et al 2021; Howard and Franklin 2016; 2015; Howard et al 2020; Howard et al 2012). While we can only speculate on the mechanism which drives this increase in adaptation, it is clear that congruent visual cues increase the adaptation to novel dynamics compared with either incongruent or the absence of visual cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such adaptation can be examined using a dual-adaptation paradigm in which participants adapt simultaneously to two different dynamics, each signalled by a contextual cue.When appropriate contextual cues are provided, humans are able to select, recall and adapt the respective model memory for each task [38][39][40][41][42][43][44][45][46]. Dual-adaptation has been shown to occur when the contextual cue is different in the physical or visual hand state [42,43], workspace visual location [43,47], bimanual or unimanual arm movements [40,48], some body postures [49] or for lead-in or follow-through movements [41,[50][51][52]. In contrast, other cues such as color provides only a weak or ineffective contextual cue for dual-adaptation [43,53], despite some studies showing a small effect [54-56].…”
mentioning
confidence: 99%